Eine Konferenz zur sozialen Frage in Basel 1869 - Pernet, Martin W. (Zwingliana, 2015)
Basle 1869. The growing industrial proletariat starts to mobilise against bad social conditions. Politically and religiously conservative factory owners hold a conference with town missionaries and clergy to seek ways of alleviating the social malaise. They urge a Christianisation of the industry based on a theological conception that emphasises the experience of individual grace. However, they fail to see the social roots of the human misery. As a result, despite all good intentions, no suitable solution can be found for the various problems.